Law Enforcement in the Crime of Crypto Asset Fraud - Moch Dimas Prasetyo; Nabila Khalisha Paramita; Trifena Julia Kambey (Budapest International Research and Critics University, 2022)
Economic development is designed to address the opportunities and needs created in economic activity. Developments in the real sector always open up opportunities for the development of the financial sector. The most dominant financial sector is the banking sector and the capital market which is one of the sources of financing for development as well as a means for improving people's welfare. The state is very important for the capital market, the development of the capital market which is a vehicle for investment and a vehicle for financing at the same time. The opportunity in question isvirtual money which then began to become a phenomenon in society since the emergence of crypto currencies (cryptocurrency) as a manifestation of technological developments in activitiese-commerce. Every time there is a good opportunity, there is also a gap in the presence of a criminal act, including activities that use digital-based crypto. The crime in question is a criminal act of fraud which clearly violates the existing law and how it is enforced. In addition to fraud, another problem is how the legal umbrella for crypto assets in Indonesia needs to be discussed in the discussion. After discussing the existing problems, of course, have a conclusion that explains briefly but completely. This research has various approaches with normative juridical research methods.